Respon Partai Islam Terhadap Organisasi LGBT: Studi Pandangan Elite Partai Islam di Kota Malang - Muniri, Akh. Syamsul; Ulfiyati, Nur Shofa (Ngabari: Jurnal Studi Islam dan Sosial, 2017)
The existence of Lesbians, Gay, Bisexual, and Transgender (LGBT) has actually existed for a long time. But many communities can not accept their existence. Peoples known as Iesbian, gay or biseksual may be tolerated in the society, but normally their own families do not want to accept them. Seeing the growing strength of LGBT organization, some Islamic based parties such as PKS will initiate bill to reject LGBT. So that Indonesia can anticipate the development of LGBT behavior. This descriptive research aims to find out the elite views of Islamic party in the Malang city about the existence of LGBT organization. And the response of the elite Islamic party in the viewing the reality of families who have LGBT members. This research is located in Malang city. The result of this research indicates that elite Islamic party worried about the existence of LGBT organizations. They see that the exixtence of LGBT organization is contrary to many norms; religius norms, law norms, customary norms, and cultural norms as easten societies. They perceive that the more existence of LGBT will undermine the the social structure. While the response of elite Islamic party to members of LGBT who refused by their families is improve and direct the LGBt members to return to the normal life. According to them government must act decisively on the issue of LGBT.LGBT members should be directed to improving conditions, they must given the right to treatment, especially psychological treatment.Keyword: elite, partai Islam, organisasi LGBT.